Comparison of MODRAT Model with Classical Rational Method, Northern Grand Method and SCS Method in Al Snobar Basin - irsak, saker; هيفا, مجد حافظ (Latakia University Journal -Engineering Sciences Series, 2025)
The study aims to compare the MODRAT model with the classical Rational method, the Great Northern method and SCS within the boundaries of the Snobar Basin, which is one of the Syrian coastal basins, by developing a mathematical model according to MODRAT, where the model was built and calibrated and the abundance at the basin outlet for the 2yr and 100yr repetition times reached a peak flow value of 252 m3/sec and 621 m3/sec respectively, and the flow values ​​were calculated according to the other methods for the same repetition times and the results were as follows: the classical Rational method 228.55 m3/sec and 544.93 m3/sec, while the Great Northern method gave maximum flow values ​​of 266 m3/s and 599 m3/s, while the application of the SCS method gave maximum flow values ​​of 128.3 m3/s and 602.58 m3/s. By comparing the results with the four methods, we find an acceptable convergence in the values, such that the error rate did not exceed 15%. This is due to the characteristics of the basin and its slopes, which gave the basin a relatively shorter concentration time. Therefore, it was possible to apply the four methods, despite the fact that the area of ​​the basin is larger than the requirements of these methods.